A Review: Feasibility Study of Bamboo Reinforced Concrete Using Calotropis Gigantea as Self- Curing Agent - Mangal, Parul; Juremalani, Jayesh (Recent Patents on Engineering, 2025)
Primarily, concrete undergoes wide self-desiccation, autogenous shrinkage, and other mechanical properties that may be influenced by inadequate curing methods. Various researchers have explored different materials for self-curing in concrete, including lightweight aggregates, water-retaining admixtures, superplasticizers, polymers, natural fibers, and pozzolanic materials, each with patented formulations capable of withstanding high-water content. These patented self-curing agents serve as infill material within the concrete, aiding in its internal curing process. Numerous tests conducted by different researchers have evaluated the efficiency and scope of self-curing in concrete, focusing on physical, mechanical, durability, and microstructural properties. Results consistently demonstrate improved concrete properties through the adoption of patented self-curing processes. The majority of research in this area has concentrated on high-performance concrete, aiming to address shrinkage issues resulting from low water-to-cement ratios. In the current research, emphasis is placed on experimentally enhancing the mechanical properties of M45 grade concrete using patented internal curing agents such as Calotropis Gigantea fibers and Polyethylene Glycol admixtures, alongside bamboo reinforcement. Calotropis Gigantea fibers, maintained at a length of 10 mm, will be added at varying percentages (0.5%, 1%, and 1.5%) by weight of the concrete. A battery of tests will be conducted to analyze different properties of concrete, which includes workability, compressive strength, flexural strength, degree of hydration, and comparative assessments against conventional concrete. Additionally, optimization of admixture dosages, intended for internal curing, will be undertaken.
Keywords: internal curing agents